2019
DOI: 10.1051/matecconf/201926804005
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study of corn cob biochar (CCBc) yield via microwave pyrolysis

Abstract: In the long-run, microwave pyrolysis can be a simpler and low energy-requiring alternative to conventional pyrolysis for the thermochemical conversion of biomass to useful products. However, there are still research gaps in its mechanism. Thus, this study investigated the various factors affecting the biochar yield using a half resolution (2k-1) factorial design on the microwave pyrolysis of corn cob wastes. A viable biochar product was produced within minutes of the reaction; wherein, the statistical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…The ANOVA result revealed that only the microwave power output and its interaction with exposure time have significant effects (p < 0.05) on the biochar yield. This is in contrast to the study by Lawas et al (2019), which reported that both factors and their interaction to be significant. The model generated is presented by the following equation: 3.…”
Section: Effect Of Microwave Power and Exposure Time On Biochar Yieldcontrasting
confidence: 99%
See 4 more Smart Citations
“…The ANOVA result revealed that only the microwave power output and its interaction with exposure time have significant effects (p < 0.05) on the biochar yield. This is in contrast to the study by Lawas et al (2019), which reported that both factors and their interaction to be significant. The model generated is presented by the following equation: 3.…”
Section: Effect Of Microwave Power and Exposure Time On Biochar Yieldcontrasting
confidence: 99%
“…This work followed the parametric study conducted by Lawas et al (2019) on the microwave pyrolysis of corncobs. Using self-purging microwave pyrolysis and polypyrrole as the absorber, the optimal settings for microwave power and exposure time were established to maximize the biochar yield from corncob.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 3 more Smart Citations